História do ensino jurídico em Alagoas: antecedentes e condicionantes de sua recente expansão - Palmeira, Lana Lisiêr de Lima (2006)
This paper looks into the recent law school boom in Alagoas and attempts to frame it against the historical, cultural, and social background of the State, providing a reasonable explanation as to the factors that have contributed to such expansion, which has rendered Alagoas the fastest growing state when it comes to newly accredited law schools. To delve into the core elements that might yield an answer to such troubling question, we embarked on a socio-anthropological study of the local society and analyzed the historical college education pattern in the state, from the birth of the first law school to the current state of affairs, devoting attention to the advances in teaching and to the reasons for this explosive growth. One factor unquestioningly stands out and makes it plain why so many students choose law among the vast array of courses offered. To understand so heightened a preference, as well as the other aspects relevant to the theme, such as how this phenomenal expansion is sensed, students from several law schools statewide and applicants from one such institution were asked to answer questionnaires. Law students and professionals were also interviewed. Based on the historical, sociological, and anthropological framework we studied, the collected data were ultimately analyzed and led us to conclude that, in view of the highly conservative nature of society regarding its culture and behavior patterns, the fascination with a career in law still prevails, imprinting on the collective psyche the idea of a highly esteemed profession, able to bestow power and prestige, which, in a patriarchal and conservative society like ours, is but a dream, a lifetime s aspiration, a goal for many.